2017
DOI: 10.1080/08958378.2017.1336585
|View full text |Cite
|
Sign up to set email alerts
|

Acute and chronicin vivoeffects of exposure to nicotine and propylene glycol from an E-cigarette on mucociliary clearance in a murine model

Abstract: Objective To determine the effect of an acute (1 week) and chronic (3 weeks) exposure to E-cigarette (E-cig) emissions on mucociliary clearance (MCC) in murine lungs. Methods C57BL/6 male mice (age 10.5 ±2.4 weeks) were exposed for 20min/day to E-cigarette aerosol generated by a Joyetech 510-T® E-cig containing either 0% nicotine (N)/propylene glycol (PG) for 1 week (n = 6), or 3 weeks (n = 9), or 2.4% N/PG for one week (n = 6), or 3 weeks (n = 9), followed by measurement of MCC. Control mice (n = 15) were n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
33
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(35 citation statements)
references
References 39 publications
2
33
0
Order By: Relevance
“…TMV reductions after a single dose lasted for ~6 hrs, upon which a repeat dose decreased TMV again. Similar findings of vapor containing nicotine on MCC were reported in a murine model (11). In contrast, that study did not find that e-cig liquid had an immediate effect on murine MCC, suggesting that the large animal is more suited to predict human responses.…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…TMV reductions after a single dose lasted for ~6 hrs, upon which a repeat dose decreased TMV again. Similar findings of vapor containing nicotine on MCC were reported in a murine model (11). In contrast, that study did not find that e-cig liquid had an immediate effect on murine MCC, suggesting that the large animal is more suited to predict human responses.…”
Section: Discussionsupporting
confidence: 71%
“…Between factors such as wattage settings for the heating element, PG/VG composition, and a user's experience with a device, a single session of inhaled vape can deliver nicotine doses that exceed those in smoke from 1 cigarette (8). Furthermore, recent efforts have partially demonstrated how PG/VG and various e-cig flavorings cause negative outcomes in vitro and in vivo such as cell death, airway inflammation, and impaired airway hydration (9)(10)(11)(12)(13)(14).…”
Section: Introductionmentioning
confidence: 99%
“…; Laube et al. ). Although we do not fully understand this phenomenon, it appears consistent across experimental settings that presence of nicotine leads to higher numbers and larger particles and, consequently, a reduced lung deposition.…”
Section: Discussionmentioning
confidence: 98%
“…Several recent studies support this finding to varying degrees. Using mice in an in vivo investigation, Laube et al ( 2017 ) determined that chronic exposure, but not acute exposure, to ECIG-generated aerosol in the presence of nicotine slowed mucociliary clearance. Kumral et al ( 2016 ) reported that individuals who use ECIG devices as a means to quit smoking produced a negative impact on sinonasal symptoms and nasal mucociliary clearance as compared to individuals who do not use ECIG devices.…”
Section: Discussionmentioning
confidence: 99%